How Biosocial Research Can Improve Interventions for Antisocial Behavior - Glenn, Andrea L. (Journal of contemporary criminal justice, 2019)
Biological factors have been found to influence the development of antisocial behavior. These factors also affect how individuals respond to the environment, including how individuals respond to interventions designed to reduce antisocial behavior. Interventions for youth with antisocial behavior may have the greatest impact if they are targeted toward youth who need it the most (e.g., those who are mostly likely to persist in their behavior problems) as well as youth who may benefit the most from the program. This article discusses potential benefits of a biosocial approach to interventions, as well as the potential ethical concerns that arise.